2021
DOI: 10.1038/s41598-021-89388-w
|View full text |Cite
|
Sign up to set email alerts
|

Urine miRNA signature as a potential non-invasive diagnostic and prognostic biomarker in cervical cancer

Abstract: MicroRNAs as cancer biomarkers in serum, plasma, and other body fluids are often used but analysis of miRNA in urine is limited. We investigated the expression of selected miRNAs in the paired urine, serum, cervical scrape, and tumor tissue specimens from the women with cervical precancer and cancer with a view to identify if urine miRNAs could be used as reliable non-invasive biomarkers for an early diagnosis and prognosis of cervical cancer. Expression of three oncomiRs (miR-21, miR-199a, and miR-155-5p) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 57 publications
0
37
0
1
Order By: Relevance
“…Intriguingly, it is estimated that 85% of cumulative CCa cases are reported from the underdeveloped economies of the world, where it is responsible for approximately 12% of altogether female cancers. Among various others, infection of HPV is a ubiquitous risk factor which is related with CCa in approximately 90% of all diagnosed cases ( Aftab et al, 2021 ). Nevertheless, the occurrence of CCa is multifactorial as it develop in a minority of women affected with HPV16 and HPV18 (high-risk CCa associated HPV strains) ( Zur Hausen, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, it is estimated that 85% of cumulative CCa cases are reported from the underdeveloped economies of the world, where it is responsible for approximately 12% of altogether female cancers. Among various others, infection of HPV is a ubiquitous risk factor which is related with CCa in approximately 90% of all diagnosed cases ( Aftab et al, 2021 ). Nevertheless, the occurrence of CCa is multifactorial as it develop in a minority of women affected with HPV16 and HPV18 (high-risk CCa associated HPV strains) ( Zur Hausen, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that miRNAs are key molecules that regulate CSCs during tumor progression [ 11 13 ]. Circulating miRNAs have the potential to serve as diagnostic markers of tumor progression and this has been the focus of an increasing number of studies [ 14 , 15 ]. For example, serum exosomal miR-1247-3p levels in patients with primary hepatic cancer are associated with the extent of lung metastasis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here we added miR-155-5p because its fold-difference was also high, especially for SCC (10-fold). At least because this score was higher than miR-20b-5p (4-fold) 15 , this was also the reason that miR-155-5p had been selected as a candidate biomarker for cervical cancer screening by others [16][17][18] . We had estimated the accuracy of screening with 4 miRNAs separately, but combining candidate miRNAs offers the possibility of further increasing accuracy 13,19 .…”
Section: Discussionmentioning
confidence: 99%